Reduction in Membrane Phosphatidylglycerol Content Leads to Daptomycin Resistance in Bacillus subtilis - Hachmann, Anna-Barbara (American Society for Microbiology, 2011)
Daptomycin (DAP) is a cyclic lipopeptide that disrupts the functional integrity of the cell membranes of Gram-positive bacteria in a Ca(2+)-dependent manner. Here we present genetic, genomic, and phenotypic analyses of an evolved DAP-resistant isolate, Dap(R)1, from the model bacterium Bacillus subtilis 168. Dap(R)1 was obtained by serial passages with increasing DAP concentrations, is 30-fold more resistant than the parent strain, and displays cross-resistance to vancomycin, moenomycin, and bacitracin. Dap(R)1 is characterized by aberrant septum placement, notably thickened peptidoglycan at the cell poles, and pleiotropic alterations at both the transcriptome and proteome levels. Genome sequencing of Dap(R)1 revealed 44 point mutations, 31 of which change protein sequences. An intermediate isolate that was 20-fold more resistant to DAP than the wild type had only three of these point mutations: mutations affecting the cell shape modulator gene mreB, the stringent response gene relA, and the phosphatidylglycerol synthase gene pgsA. Genetic reconstruction studies indicated that the pgsA(A64V) allele is primarily responsible for DAP resistance. Allelic replacement with wild-type pgsA restored DAP sensitivity to wild-type levels. The additional point mutations in the evolved strain may contribute further to DAP resistance, serve to compensate for the deleterious effects of altered membrane composition, or represent neutral changes. These results suggest a resistance mechanism by which reduced levels of phosphatidylglycerol decrease the net negative charge of the membrane, thereby weakening interaction with the positively charged Ca(2+)-DAP complex.